Urease activity and urea hydrolysis rate under coupling effects of moisture content, temperature, and nitrogen application rate - Lei, Tao; Gu, Qiongqiong; Guo, Xianghong; Ma, Juanjuan; Zhang, Yong; Sun, Xihuan (International Journal of Agricultural and Biological Engineering, 2018)
The traditional qualitative analysis of the individual factors on the kinetic parameters cannot sufficiently reveal the mechanism underlying urea hydrolysis in soil. This study aimed at revealing the coupling effects of the three factors on urease activity (V0), hydrolysis rate constant (Ku), and activation energy (Ea) and establishing the quantitative model for Ku under the coupling condition. Laboratory culture experiments were conducted under different temperatures (T) (15°C, 20°C, 25°C, and 35°C), moisture contents (θ) (60%, 80%, and 100% of field capacities), and nitrogen application rates (F) (247 mg/kg, 309 mg/kg, 371 mg/kg, and 433 mg/kg). The urea content was measured daily. Results showed that the effects of moisture content, temperature, nitrogen application rate, and their interaction on V0 and Ku were in the descending order: T, F, T*F, θ, T*θ, F*θ, T*θ*F. The effect of single factor and two-factor coupling on V0 was extremely significant (p<0.01), whereas the effect of the three-factor coupling on V0 was negligible. The effects of three factors and their interaction on Ku were extremely significant (p<0.01). The effects of moisture content, nitrogen application rate, and their interaction on Ea were in the descending order: F, θ, F*θ. The effects of two factors and their interaction on Ea were not significant. The mean absolute percentage error (MAPE) values of the established Ku-1 (θ, T, F) and Ku-2(θ, T, F) models were 3.14% and 4.60%, respectively. The MAPE of the traditional Arrhenius model Ku-3(T) was 6.75%. The accuracy of the proposed three-factor interaction model was superior to that of the traditional single factor model. The results supplemented the mechanism of urea hydrolysis and improved the prediction accuracy of Ku. Keywords: urease activity, hydrolysis rate constant, Arrhenius model, activation energy, coupling effect DOI: 10.25165/j.ijabe.20181102.3784 Citation: Lei T, Gu Q Q, Guo X H, Ma J J, Zhang Y, Sun X H. Urease activity and urea hydrolysis rate under coupling effects of moisture content, temperature, and nitrogen application rate. Int J Agric & Biol Eng, 2018; 11(2): 132–138.